Construction of a Artificial Glutathione Peroxidase with Temperature‐Dependent Activity Based on a Supramolecular Graft Copolymer. Issue 4 (12th February 2015) - Yin, Yanzhen; Jiao, Shufei; Wang, Yun; Zhang, Ruirui; Shi, Zhongfeng; Hu, Xiaoxi
Abstract A supramolecular artificial glutathione peroxidase (PNIPAM‐CD‐g‐Te) was prepared based on a supramolecular graft copolymer. PNIPAM‐CD‐g‐Te was constructed by supramolecular host–guest self‐assembly. Significantly, PNIPAM‐CD‐g‐Te displayed noticeable temperature‐dependent catalytic activity and typical saturation kinetics behavior. It was also proved that the change in the self‐assembled structure of PNIPAM‐CD‐g‐Te during the temperature‐dependent process played a significant role in the temperature‐dependent catalytic behavior. The construction of PNIPAM‐CD‐g‐Te based on supramolecular graft copolymer endows artificial GPx with temperature‐dependent catalytic ability, enriched catalytic centers, and homogeneously distributed catalytic centers. This work bodes well for the development of other biologically related host–guest supramolecular biomaterials.